Laboratory Study on the Use of Novel Biodegradable Scale Inhibitors Against Mixed Calcium Carbonate and Calcium Sulfate Scale - Husna, U.Z. (2022)
The development of the scale layers in oil and gas operation results in production losses and equipment instability because of pipeline blockage, energy leak, corrosion acceleration and severe accidents which will impact the safety of production. Among many types of scales, calcium carbonate and calcium sulfate are considered the most frequent, prominent and terrible. On the other hand, cellulose is a class of natural polymers and also contains abundant functional groups including hydroxyl, carboxyl, and amino groups, resulting in good chelation and dispersion effects. They possess good physical and chemical properties, thermal stability, and biodegradability, abundantly available and inexpensive which make them promising compounds for the creation of "green" oil field reagents, including scale inhibitor. In this study, we tested two types of biodegradable polymers named hydroxyethyl cellulose (HEC) and carboxymethyl cellulose (CMC) for application as calcium carbonate and mixed carbonate and sulfate inhibitors. There are three methods carried out, starting from the thermal stability test, static bottle test, and dynamic scale loop test. The inhibition performance tests were done at temperatures of 50°C, 70°C, and 90°C. The inhibitor concentration was varied from 10, 50, 100, 1000 until 10000 ppm. The results indicate that both HEC and CMC have the potency to be used as inhibitors for these two types of scales. Both results from the static bottle test and dynamic scale loop test indicate that HEC and CMC were able to inhibit the formation of the tested scale, yet they have not been able to completely inhibit 100 of scale formation. Copyright © 2022, Offshore Technology Conference.